The Implementation Of Genre-Based Approach In Teaching Speaking To The Eighth Grade StudentsAt Smp Muhammadiyah 4 SurakartaIn 2015/2016 Academic Year - Satiti Hapsari, Tia, Mauly Halwat Hikmat, Ph.D, Siti Fatimah, M. Hum (2017)
This research aims at (1) describing the materials used in teaching speaking by using Genre Based Approach in SMP Muhammadiyah 4 Surakarta (2) the procedures used in teaching speaking using GBA (3) problems faced by the teacher in using GBA. The methods of collecting data are observation, interview and documentation. The subject of the study is eight grade students at SMP Muhammadiyah 4 Surakarta in academic 2015/2016. This research uses descriptive qualitative where is the process of simplification of data to make easier to read. The writer gets the data of this research from event, informant and document. The methods of analysis data are BKOF, MOT, JCOT, and ICOT. The result of the analysis shows that the materials used by the students in the classroom is a handbook of the students. The procedures are building knowledge of field, modeling of text, joint construction of text, and independent construction of text. The problems faced by the teacher in using GBA are the students lack of mastering vocabulary, different capability of the students. Keyword: Genre Based Approach